Analysis of Indonesian Domestic Tourist Quality: Case Study: Domestic Tourist Digital Survey 2021 - Martha Zalukhu; Neli Agustina (Proceedings of The International Conference on Data Science and Official Statistics, 2023)
Domestic tourism is being the main focus of the government strategy to revitalize the tourism sector. It is then crucial to consider elements that can raise the quality of tourism, in terms of domestic tourists and increase the added value rather than merely number of trips. The analysis of quality is important in tourism to support the idea of sustainable tourism, which is promoted in the 8th agenda of Sustainable Development Goals (SDGs). Quality analysis must be done in micro modelling that takes into account tourist characteristics and particular travel-related features because this sector depends on tourism demand and tourist expenditure in tourist locations. Thus, the goal of this study is to give a general overview of the qualities and characteristics of domestic tourists and to examine how these attributes affect their quality. The results of descriptive analysis method indicate that Indonesian domestic visitors’ quality remains poor. Age, genders, education level, employment status, transportation mode, accommodation type and travel companion affect the quality of domestic tourists.